The Mediating Role of Electronic Word of Mouth on the Relationship between Sport Event Tourism, Hedonism, and Tourists’ Visit Intention: Evidence from MotoGP Mandalika - Rachman, Ghina Aurelia; Furkan, Lalu Muhammad (Indonesian Journal of Advanced Research, 2025)
This study examines how sport event tourism and hedonism influence tourists’ visit intention, with electronic word of mouth (eWOM) as a mediating variable. Using a quantitative approach, data were collected through offline interviews with 100 visitors of the MotoGP Mandalika event and analyzed using PLS-SEM. Results show that sport event tourism and hedonism significantly affect eWOM, while only sport event tourism and eWOM directly influence visit intention. eWOM also mediates both relationships, suggesting that emotional enjoyment and digital engagement transform experiences into behavioral intentions. These findings highlight the strategic importance of enhancing event quality and encouraging online sharing to strengthen destination image and revisit intention in sport tourism contexts.